The regularities of multibeam acoustic waves interference in MEMS cavity-type structures without shear stress. Analysis by the envelope method - Kosoboutskyy, P.; Karkulovska, M. (Видавництво Львівської політехніки, 2012)
In this paper the amplitude-phase spectra envelope method of multi-beam acoustic waves Fabry-Perot interference in MEMS cavity-type structures without shear stress at normal and oblique beam passing limits divisions is developed. It is found that the spectra analysis by the envelope method significantly broadens the application of an appropriate approach for nondestructive testing of thin film structure parameters. In addition, on the basis of the envelope function regularities the angular conditions of Pseudo effect manifestation for the binary interface in the spectra are grounded. Розроблено метод обвідних амплітудно-фазових спектрів багатопроменевої інтерференції Фабрі-Перо акустичних хвиль для МЕМС-структур резонаторного типу без зсувних напруг при нормальному і похилому проходженні променем меж поділів. Встановлено, що аналіз спектрів методом обвідних істотно розширює межі застосування відповідного підходу для організації неруйнівного контролю параметрів плівкових структур. Крім цього, на основі закономірностей обвідних обґрунтовано кутові умови прояву в спектрах псевдобрюстерівського ефекту для бінарної межі поділу.
Keywords: MEMS-structures; Fabry-Perot interference; amplitude-phase spectra; МЕМС-структури; інтерференція Фабрі-Перо; амплітудно-фазові спектри